Retinoblastoma cell-derived exosomes promote angiogenesis of human vesicle endothelial cells through microRNA‐92a-3p - Chen, Shuilian (Cell Death Dis, 2021)
Exosomes derived from tumor cells play a key role in tumor development. In the present study, we identified the bioactivity of exosomes released from WERI-Rb1 retinoblastoma cells in tumor angiogenesis, as well as the underlying mechanism, through biochemical methods and animal experiments. Our in vitro data showed that exosomes could be engulfed by human vesicle endothelial cells (HUVECs), significantly promote cell viability and induce an inflammatory response in HUVECs by increasing the expression of a series of related genes, such as IL-1, IL-6, IL-8, MCP-1, VCAM1, and ICAM1. Significant increases in migration and tube formation were also observed in the HUVECs incubated with exosomes. Moreover, experiments with a nude mouse xenotransplantation model showed that exosomes injected near tumors could be strongly absorbed by tumor cells. The numbers of endothelial cells and blood vessels were significantly increased in tumor tissues treated with exosomes compared to control tissues. Furthermore, to reveal the mechanism underlying exosome-mediated angiogenesis in retinoblastoma, we analyzed the levels of 12 microRNAs in the exosomes. Specifically, our data showed that miR-92a-3p was enriched in RB exosomes. Accordingly, miR-92a-3p was increased in the HUVECs incubated with these exosomes. After treatment with a miR-92a-3p inhibitor, the promoting effect of exosomes on the migration and tube formation of HUVECs was significantly abrogated. The expression of the angiogenesis-related genes mentioned above was markedly decreased in HUVECs. Similarly, treatment with a microRNA mimic also demonstrated that miR-92a-3p was involved in the angiogenesis of HUVECs. More importantly, bioinformatics analysis predicted that Krüppel-like factor 2 (KLF2), a member of the KLF family of zinc-finger transcription factors, might be an active target of miR-92a-3p. Notably, this prediction was confirmed both in vitro and in vivo. Thus, our work suggests that exosomal miR-92a-3p is involved in tumor angiogenesis and might be a promising therapeutic candidate for retinoblastoma.